Meningkatkan Motivasi Belajar Dan Kemampuan Pemecahan Masalah Matematis Siswa SMP Melalui CTL - ., Saepuloh (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
This study is an experimental study with pretest-posttest control group design that purposes to know: (1) the achieving and improving of students’ motivation and mathematical solving problem with CTL and its differences to the student who get conventionally, (2) the correlation between the achieving and improving of students’ motivation and mathematical solving problem. The population in this study is the students of SMPN 2, one class is given CTL and other class conventionally. The instrument that is used in this study is the ability mathematical problem solving and motivation questionnaires with scale of likert. The data analysis is used quantitative method. The conclusion: (1) there is significance difference of study motivation and the achieving of student mathematical problem solving between CTL and conventional student, (2) there is significance difference the improving of student mathematical problem solving between CTL and conventional student, and (3) there is significance correlation between student motivation and the achieving of students’ mathematical problem solving.